DERMATITE ATOPICA: REVISÃO ACERCA DA ETIOLOGIA, TRATAMENTO E DIAGNOSTICO (REMUNOM, 2025)
Atopic dermatitis (AD) is a chronic condition characterized by chronic inflammation, intense pruritus, xerosis, and recurrent eczematous lesions. Its etiology, in turn, has genetic, immunological, and environmental causes. This disease is significantly associated with other atopic conditions such as asthma and allergic rhinitis. The diagnosis is clinical and made using the Hanifin and Rakja criteria, and treatment should be done through skin hydration and management of triggering factors. This article aims to review the main aspects of AD, including: pathophysiology, diagnosis, and therapeutic strategies.